Oral clinical factors affecting self-perception of oral health - Nogo-Živanović Dajana; Kulić Ljiljana; Žuža Aleksandra; Davidović Brankica; Radović Igor (Serbian Medical Society - Dental Section, Belgrade, 2015)
Introduction Self- assessment of oral health is simple, non-invasive and cost-effective method of collecting data that takes into account psychosocial aspects of oral health. The aim of this study was to investigate the effect of clinical factors on the self-perception of oral health in middle-aged patients in Republika Srpska (Bosnia and Herzegovina). Material and Methods The study included 126 subjects of both genders (34.1% male and 65.9% female) aged 24-54 years. Data were collected through questionnaires and clinical examination. Anonymous questionnaire contained questions related to socio-demographic characteristics of respondents. Clinical examination included teeth condition and the presence of prosthetic restorations. Self-perception of oral health was determined by one question. Results Bivariate analysis indicated significant effect of carious (p<0.001), missing (p<0.001) and filled teeth (p=0.022) but not the prosthetic status on self-perception of oral health. Correlation between the number of carious and missing teeth with self-perception of oral health was significant in regression analysis. Conclusion The number of carious and missing teeth had significant impact on self-assessment of oral health in studied population. Knowledge of effects of oral clinical variables on self-perception of oral health is very important to obtain clearer insight into the association between objectively and subjectively assessed oral health.